Hybridization-activated new deep ultraviolet transparent nonlinear optical material Ba11[Al(PO4)4](P2O7)(PO4)3 with balanced overall performance and parsimony-forbidden structure. Issue 48 (3rd December 2019) - Fang, Zhi; Yang, Bingping; Hu, Chunli; Mao, Jianggao
Abstract : Hybridization-enabled approach of a new deep-ultraviolet transparent nonlinear-optical material Ba11 [Al(PO4 )4 ](P2 O7 )(PO4 )3 exhibiting balanced overall performance and featuring three types of chromophores. Abstract : A new nonlinear optical material, Ba11 [Al(PO4 )4 ](P2 O7 )(PO4 )3, was rationally synthesized via the hybridization of three types of anionic groups, namely [AlO4 ] 5−, [PO4 ] 3− and [P2 O7 ] 4−, via a spontaneous nucleation method. Ba11 [Al(PO4 )4 ](P2 O7 )(PO4 )3 was characterized with high thermal stability, deep ultraviolet transparency and moderate second-order optical nonlinearity, which were favourable for practical applications.